Effect of Sintering and Concentration of Dymethylformamide on Surface Properties of Hydroxyapatite Coating on Titanium Substrate Fabricated by Electrophoretic Deposition - Mochammad Dachyar Effendi; Razie Hanafi; Utari Pusparini; Sara Aisyah Syafira (Universitas Negeri Surabaya, 2020)
Hydroxyapatite (HAp) coating on metallic implant was developed to increase bioactivity of orthopaedic implant. In this work, hydroxyapatite was successfully deposited on commercially pure titanium (CP-Ti) substrate by electrophoretic deposition (EPD). This work aims to determine the effect of dimethylformamide (DMF) as dispersant for EPD suspension followed by heat treatment, on the surface morphology of the HAp coating. HAp powder was suspended in an ethanol-DMF solution with the amount of DMF designed at 0, 5, 10, and 15% per 100 mL suspension. EPD was then performed successfully on all samples. After EPD, the specimens were sintered at 800 °C for 120 minutes in argon atmosphere. Surface morphology, composition, and phase of HAp coating before and after sintering were characterized by Scanning Electron Microscope, Fourier Transform Infrared Spectrometer, and X-ray Diffractometer. X-ray and IR spectra confirmed that sintering had a little effect on the chemical structure and the phase of the deposited HAp. The morphology of the surface is denser across all samples and shows distinguishable features as the amount of DMF in the system was increased. The 15% DMF sample exhibits the mostly grooved surface after sintering. Further analysis showed that sintering reduced the EPD-related shrinkage on the surface and enhanced the size of the pores. Microstructural indication referring to previous research suggested that this type of microscopic surface is very sought after in promoting a good biological interaction between the implant and the host. Further testing must be done to confirm the effect of DMF-modified structure in living tissue.